The optimal placement model for electric vehicle charging stations using bayesian networks - Sai Siddarth Reddy M.; Sai Venkata Nitin B.; Narayana Garlapati (MATEC Web of Conferences, 2024)
As costs rise and fossil fuels have harmful environ- mental effects more and more people choose electric cars or electric cars this change shows how electric cars are becoming more and more popular in the transportation industry as their fleet grows it becomes clear that more infrastructure is required for charging the first step in the optimization method of this study which aims to identify ideal locations for stations considering user accessibility and investment costs is to identify potential charging locations and places are carefully studied using mixed integer linear programming MLP techniques to identify optimal locations based on historical EV paths the study examines this complex urban environment.